FROM NDC TO REALITY? AN ANALYSIS OF THE TRAJECTORY OF BRAZILIAN GREENHOUSE GAS EMISSIONS BETWEEN 2015 AND 2023 IN LIGHT OF ULRICH BECK'S RISK SOCIETY (REMUNOM, 2025)
The article's primary objective is to analyze Greenhouse Gas (GHG) emissions in Brazil between 2015 and 2023 in relation to the targets of the first Nationally Determined Contribution (NDC), using Ulrich Beck's sociological perspective on the Risk Society. Data analyses utilized information from the SEEG (System of Estimates of Emissions and Removals of Greenhouse Gases), identifying that although Brazil committed to a 37% reduction in emissions by 2025 compared to 2005, the results remained insufficient, primarily due to deforestation and agriculture. In this context, it is evident that between 2019 and 2022, the weakening of environmental policies intensified the deviation from the target. In 2023, with the resumption of enforcement, deforestation was reduced, contributing to a significant drop in emissions, although a further cut of approximately 25% over two years is still required to meet the NDC. Thus, the sociological analysis highlights that climate risks, which are socially produced, most severely affect vulnerable populations but ultimately rebound upon society in a generalized manner through the "boomerang effect" as explained by Beck.